Dimensions of intellectual references and the format of the occasion in the poetry ofabdelhamid Ben Badis a reading of the contents and poetic image (مجلة إحالات, 2026)
The efforts of the elders of the Algerian Free Association of Scholars during the colonial period did not stand in the way of resistance to the cultural monastery practised in its people with awareness, roots and guidance But it recruited its pens to exhaust the absent energies by cultivating the authentic memory of thecultural effort by means of the original creative affiliation ink of poetry, In a state of tendency to bepsychologically calm in the process of creativity s creativity and poetry, and the leisure space remained at its narrowest practice. and the effort of national formation projects and creativity in marginalized scientists'products.In the light of this paper, the Elder of Algerian Scholars Abdelhamid Ben Badis' project, when he wasable to represent the house of literature and blow it out of his soul to provoke the vagueness of creativityamong the creators of literature, was the facade of thinking to give away part of our national creativity, heardthe voice of a nation and sent breath messages to those who lived on the margins of life absent.